La concurrence déloyale en droit international privé communautaire - Coureault, Elisabeth (Université Nancy 2, 2009)
Indisponible
Keywords: Competencia; Competition law; Concurrence déloyale; Droit international privé (droit européen); Droit international privé communautaire

Les fondements épistémologiques du mouvement Law & Economics - Lanneau, Régis (Université Paris 10, 2009)
La présente thèse vise à montrer que l'analyse économique du droit est une philosophie du soupçon, un système logique d'interprétation des phénomènes juridiques qui peut nous apporter des connaissances si nous prenons bien en compte sa qualité de système d'interprétation. Les propositions économiques étant largement analytiques, elles peuvent nous informer uniquement par les questions qu'elles suscitent. Le raisonnement économique est tout d'abord un code de perception qui se fonde sur deux concepts : la rationalité et l'efficience. Ce code de perception nous donne des intuitions qui « semblent » pertinentes pour l'étude du droit (à la fois sur ce qu'est le droit l'approche du raisonnement juridique). Se pose alors la question de ce qui fait la « validité » des connaissances proposées. Des considérations a priori ou des considérations empiriques semblent insuffisantes pour rendre compte de la pertinence de ce type d'analyse. Nous proposons finalement une approche en termes de renversement : ce n'est qu'en que le code n'est qu'un code et en confrontant ses propositions à d'autres points de vue que nous pouvons espérer gagner des « connaissances ». L'analyse économique du droit pose aussi la question de l'analyse juridique du droit.
Keywords: Analyse économique du droit; Droit (aspect économique); Droit (philosophie); Logique juridique; Pragmatisme (philosophie); Épistémologie des sciences sociales

A Critique of Trade Disputes Settlement Mechanism in Nigeria: 1968 to 2004 - Anyim, Francis Chukwudike (University of Lagos, 2009)
Full texts attached
https://ir.unilag.edu.ng/handle/123456789/4419
Keywords: Conflict Manifestation; Labour market research; Marxist Perspective; Process of Collective Bargaining; Strike and its effect

La place de la victime dans le procès pénal - Corioland, Sophie (Université de Strasbourg, 2009)
Ayant souffert d’une infraction, la victime a le droit de demander réparation du préjudice subi en exerçant l’action civile. Le droit français lui offre la possibilité d’agir devant le juge pénal, même sans demande d’indemnisation. La victime devient ainsi une partie à l’instance. Cette qualité de partie civile peut également être octroyée à des structures associatives pourtant non victimes de l’infraction. Or, les droits qui accompagnent le statut de victime, constituée ou non, se sont considérablement renforcés au cours des trente dernières années. La partie lésée jouit désormais de possibilités d’action étendues à tous les stades de l’instance. En outre, le législateur a modifié certaines règles procédurales pour adapter le procès à ce nouvel acteur, même si quelques aménagements sont encore souhaitables. Cependant, la consécration d’une telle place a entraîné un bouleversement dans le déroulement de l’instance, au détriment des droits des autres parties. Des limites doivent donc être apportées dans l’octroi du statut de partie civile et dans l’exercice des droits subséquents. Il en va de l’équilibre du procès pénal.
Keywords: France; Justice réparatrice; Procédure pénale; Victimes d'infractions

L'intervention de l'assureur au procès pénal : contribution à l’étude de l’action civile - Schulz, Romain (Université Nancy 2, 2009)
L’intervention de l’assureur au procès pénal concerne l’assureur de la victime, du prévenu ou de l’accusé, ou du civilement responsable. C’est alors en tant que garant de l’indemnisation du dommage de l’infraction que l’assureur intervient. Il participe donc à l’action civile intentée devant le juge répressif plutôt qu’au procès pénal, lequel porte d’abord sur l’action publique et éventuellement sur l’action civile. La question de l’intervention de l’assureur au procès pénal est indissociablement liée à celle de l’action civile exercée devant le juge répressif. En droit positif, le principe est que l’assureur est exclu du procès pénal, en application d’une jurisprudence stricte fondée sur les dispositions du Code de procédure pénale (notamment de son article 2). Toutefois, la loi du 8 juillet 1983 a introduit dans le Code de procédure pénale une intervention de l’assureur, admise de manière limitée tant dans son champ d’application que dans son objet et ses effets. Ce régime est révélateur de la conception de l’action civile qui prévaut en droit français. Ces solutions du droit positif méritent d’être soumises à un examen critique. L’analyse critique de l’intervention de l’assureur au procès pénal passe par un renouvellement de l’analyse de l’action civile, qui permet d’envisager successivement le principe de la participation de l’assureur aux débats devant le juge répressif et le régime de l’intervention de l’assureur à l’action civile, afin de proposer des solutions plus simples et plus efficaces.
Keywords: Assureur; Compagnies d'assurances; Recours subrogatoires; Tiers (droit); Tiers-payeurs; Victime d’infraction

Les politiques de transport routier dans la Communauté économique et monétaire de l’Afrique centrale - Robenate, Jean-Calvin (Université Lumière Lyon 2, 2009)
La Convention régissant l’Union économique de l’Afrique centrale (UEAC) renferme les dispositions particulières dont l’objet est d’harmoniser les politiques de transports. Cela passe par l’ouverture des marchés nationaux des Etats membres aux opérateurs économiques, la suppression des restrictions à la libre prestation des services et d’établissement, l’interconnexion des infrastructures, etc. A partir des critères de validité formelle, factuelle et axiologique du droit, cette thèse a pour objet d’analyser les contraintes qui handicapent ces politiques. Après avoir fait le constat des difficultés liées au choix de la technique d’harmonisation des droits, l’étude se penche sur les limites dues à la non-observation des procédures d’admission des conventions dans les ordres juridiques internes, à la faiblesse des institutions, aux risques économiques, financiers et politiques. Elle suggère qu’il est nécessaire de remettre de l’ordre dans les systèmes juridiques, grâce à une politique de codification et, à terme, de rechercher la sécurité juridique, par l’uniformisation des règles en présence. Enfin, face à la corruption, elle prend position pour un devoir d’ingérence de la Communauté internationale pour sécuriser les ressources destinées à la modernisation des infrastructures routières.
Keywords: Afrique centrale; CEMAC; Codification du droit; Coding of the right; Communauté Economique et Monétaire de l'Afrique Centrale; Contraintes juridiques; Devoir d’ingérence; Free competition; Freedom of movement; Intégration économique; Legal constraints; Libre circulation; Libre concurrence; Politique publique; Security of the financing of the infrastructures; Standardization of the right; Sécurisation du financement des infrastructures; Technique d’harmonisation; Technique of harmonization; To have of interference; Transport routier; Unification internationale; Uniformisation du droit; Validity of the right; Validité du droit

The relevance of prior use in trade mark conflicts - Alberts, Riaan Willem (University of South Africa, 2009)
This thesis investigates the role of prior use in common and statutory trade mark law. In the United States a pertinent requirement is priority of use. In the United Kingdom and South Africa, a reputation must be present. In the United Kingdom a plaintiff is required to have goodwill in the country, but in the United States and South Africa it is not required. The conception of a mark does not qualify for protection. It is not required that a business must have actually entered the market. In the United States the general approach is that a plaintiff will not receive protection in a remote area, but regard must be had to zones of natural expansion. British and South African law is the same, and protection may be obtained in areas where there is no trading. Where a dual reputation exists, neither party will be able to act against the other. The mere fact that the user of a mark was aware of the use thereof by another person, does not exclude protection. A trade mark application can be opposed on the basis of another application, combined with use of a mark, or on the ground of prior use. In some instances the fact that a mark has been filed will influence the burden of proof. In general, a registration can be expunged on the same grounds as would constitute grounds of opposition. The concurrent use of a mark can form the basis for the registration of a mark. In the United States, the use must have taken place prior to the filing date of the other party, but in the United Kingdom and South Africa, prior to the own filing date. In the latter two countries, knowledge of a mark is not necessarily exclusionary. Prior use is generally accepted as a defence to an infringement action. It is, however, noted that in various countries, it is only use prior to the relevant date that will be protected, and there is not necessarily a right to extend the scope of use concerned.
Keywords: Common law trade marks; Competencia; Competition law; Intellectual property; Trade marks; Unfair competition; Unlawful competition

Selective legal aspects of bank demand guarantees - Kelly-Louw, Michelle (University of South Africa, 2009)
Bank demand guarantees have become an established part of international trade. Demand guarantees, standby letters of credit and commercial letters of credit are all treated as autonomous contracts whose operation will not be interfered with by courts on grounds immaterial to the guarantee or credit itself. The idea in the documentary credit transaction/demand guarantee transaction is that if the documents (where applicable) presented are in line with the terms of the credit/guarantee the bank has to pay, and if the documents do not correspond to the requirements, the bank must not pay. However, over the years a limited number of exceptions to the autonomy principle of demand guarantees and letters of credit have come to be acknowledged and accepted in practice. In certain circumstances, the autonomy of demand guarantees and letters of credit may be ignored by the bank and regard may be had to the terms and conditions of the underlying contract. The main exceptions concern fraud and illegality in the underlying contract. In this thesis a great deal of consideration has been given to fraud and illegality as possible grounds on which payment under demand guarantees and letters of credit have been attacked (and sometimes even prevented) in the English, American and South African courts. It will be shown that the prospect of success depends on the law applicable to the demand guarantee and letter of credit, and the approach a court in a specific jurisdiction takes. At present, South Africa has limited literature on demand guarantees, and the case law regarding the grounds upon which payment under a demand guarantee might be prevented is scarce and often non-existent. In South Africa one finds guidance by looking at similar South African case law dealing with commercial and standby letters of credit and applying these similar principles to demand guarantees. The courts, furthermore, find guidance by looking at how other jurisdictions, in particular the English courts, deal with these issues. Therefore, how the South African courts currently deal/should be dealing/probably will be dealing with the unfair and fraudulent calling of demand guarantees/letters of credit is discussed in this thesis.
Keywords: Bank guarantee; Demand guarantee; Documentary credit; Fraud; Freezing injunction; Garantie bancaire; Letters of credit; Suretyship and guaranty

A tutela jurídica do capital intelectual das sociedades empresárias - Abdallah, Ana Claudia Karam (Universidade de São Paulo, 2009)
Na atual era pós-industrial, o conhecimento passa a ser o principal fator de produção da economia. De fato, ele confere à empresa seu maior diferencial competitivo no mercado globalizado: a inovação, ou seja, a capacidade de, continuamente, gerar novos produtos, processos e serviços ou aperfeiçoar os existentes. A organização da empresa em sociedade empresária possibilita a criação de conhecimento coletivo oriundo do trabalho profissional dos seus sócios, administradores e empregados, fato que originou a expressão capital intelectual, cunhada no âmbito econômico para designar o patrimônio empresarial de natureza intangível resultante de contribuições intelectuais. Como o Direito é precedido da evolução das sociedades e da Economia, nota-se a importância de sempre se buscarem soluções jurídicas às novas realidades socioeconômicas que surgem ao longo da história. Diante disso, a análise da natureza jurídica e das formas de tutela do capital intelectual torna-se imperativa para a identificação e apropriação privada desse patrimônio pela sociedade empresária, seja por meio do exercício de direitos de exclusivo, seja pela implementação de mecanismos de governança capazes de assegurar a diferenciação da atividade empresarial no mercado e a necessária coibição de práticas de concorrência desleal. In the current post-industrial age, knowledge becomes the main production factor of the economy. Indeed, it provides the company with its main competitive advantage in the globalized market: the innovation, that is, the capacity of continuously generating new products, processes and services or enhance the existing ones. The companys organization as business company allows the creation of collective knowledge arising from the professional work of its partners, officers and employees, which fact originated the term intellectual capital, created in the economic scope to designate the corporate equity of intangible nature resulting from intellectual contributions. As the Law came after the evolution of the companies and of the Economics, it is noted the importance of the constant search for legal solutions, the new socioeconomic realities that appear along the history. In view of that, the analysis of the legal nature and of the forms of protection of the intellectual capital becomes critical for the identification and private appropriation of such equity by the business company, either by means of the exercising of exclusive rights or by the implementation of governance mechanisms capable of ensuring the differentiation of the corporate activity in the market and the required restraining of unfair competition practices.
Keywords: Capital social; Concorrência desleal; Direito empresarial; Estabelecimento comercial; Intangible; Intellectual capital; Intellectual property; Propriedade intelectual; Sociedade comercial; Unfair competition

O Estado como acionista controlador - Pinto Junior, Mario Engler (Universidade de São Paulo, 2009)
O presente trabalho acadêmico procura construir um referencial teórico baseado no ordenamento jurídico brasileiro para definir o papel da empresa estatal no mundo contemporâneo. Trata-se do ponto de partida para compreender a atuação do Estado como acionista controlador e as regras de convivência com acionistas privados em posição minoritária e com outros grupos de interesse afetados pela atividade empresarial. A abordagem do tema apóia-se na idéia central de que toda empresa estatal está investida de uma missão pública, explícita ou implicitamente incorporada no objeto social, que varia conforme a natureza da atividade exercida e está sujeita a adaptações ao longo do tempo. A missão pública coexiste com a finalidade lucrativa inerente ao modelo de companhia e serve para condicionar a ação do Estado enquanto acionista controlador e dos administradores, dando conteúdo a seus deveres fiduciários. This dissertation aims at establishing a theoretical framework according to Brazilian law to identify the role of state-owned enterprise in contemporary world. This is the first step to understand what the governments behavior should be as a controlling shareholder and the legal rules applied to its relationship with equity investors and others stakeholders. The approach is based on the assumption that every state-owned enterprise has a public mission implicitly or explicitly included in its bylaws objectives. The public mission varies according to the nature of the business and should be redefined from time to time to keep adherence to the external environment. The public mission coexists with the companys profit scope and guides the States actions, as well as those of directors and officers. For that reason the public mission is embedded in their fiduciary duties.
Keywords: Acionista majoritário; Actionnaire majoritaire; Board of directors; Conselho de administração; Controle acionário; Controlling shareholder; Corporate governance; Empresas públicas; Entreprise publique commerciale; Etat; Fiduciary duties; Governança corporativa; Mixed capital corporation; Public interest; Sociedade de economia mista; State-owned enterprise

Réflexions sur le concept de bien juridique protégé par le droit pénal - Marion, Lacaze (Université Montpellier 1, 2009)
Réfléchir sur le concept de bien juridique protégé par le droit pénal, c’est s’interroger sur l’objet de protection de celui-ci et, parallèlement, sur l’objet de l’atteinte causée par le comportement prohibé. Pilier de la théorie de l’infraction en Allemagne et dans les nombreux pays qui l’ont prise pour modèle comme l’Espagne ou l’Italie, le bien juridique n’intéresse que peu les auteurs français. Le contraste est alors frappant entre la multitude d’études qui lui sont consacrées à l’étranger et l’absence de recherche d'un concept véritable par la doctrine française. Les principes fondateurs du droit pénal moderne que sont le principe de légalité et le principe d’interprétation stricte semblaient interdire de l’envisager sous un angle autre que formel. Mais la dérive vers un droit pénal du danger a révélé les faiblesses des garanties traditionnelles comme l’impuissance des outils théoriques classiques pour analyser les évolutions d’une matière pénale mouvante aux frontières de plus en plus troublées. Face aux menaces qui pèsent sur les garanties premières que sont le principe de légalité criminelle et le principe de la responsabilité subjective, il a alors paru indispensable de refuser de réduire le droit pénal à sa fonction de conservation du système social et de replacer, à l’image des systèmes d’inspiration germanique, la question de sa finalité au cœur de la réflexion juridique. L’adoption d’une définition matérielle du bien juridique protégé, non par la détermination illusoire d’une liste de biens juridiques a priori dignes de protection pénale mais par la reconnaissance de l’indéniable contenu axiologique de la loi pénale, offre, outre la perspective d’une analyse critique du droit positif, un cadre théorique nouveau permettant de mieux comprendre ses enjeux et ses évolutions. Sans renoncer aux garanties essentielles du principe de légalité, l’infraction se trouve repensée autour de la distinction fondamentale entre injuste (comportement typique antijuridique) et imputation de l’injuste. La qualification de l’injuste, soumise à une appréciation axiologique objective, est ainsi dissociée de la question de son imputation, ce qui permet de réaffirmer l’exigence de responsabilité subjective du sujet actif tout en préservant et en encadrant les prérogatives du sujet passif. ___ PARTIE I : De la reconnaissance du concept Titre 1 : Le bien juridique et la loi Chapitre 1 : Une nature juridique discutée Chapitre 2 : Une existence juridique incertaine Titre 2 : Le bien juridique et le fait Chapitre 1 : Le caractère protéiforme du bien juridique Chapitre 2 : La crise prétendue du concept PARTIE II : De l’intégration du concept dans la théorie de l’infraction Titre 1 : L’atteinte au bien juridique, condition de l’injuste Chapitre 1 : La reconstruction du concept Chapitre 2 : La qualification de l’injuste Titre 2 : L’injuste, élément qualifiant de l’infraction Chapitre 1 : L’imputation de l’injuste au sujet actif Chapitre 2 : L’injuste, fondement de l’action du sujet passif
Keywords: Antijuridicité; Bien juridique; Biens juridiques; Droit pénal; Droit pénal de l'ennemi; Exigibilité; Imputation; Infraction

Les Incidences de la diversification des valeurs mobilières sur le droit de vote dans les sociétés par actions - Traoré, Assétou (Université d'Auvergne - Clermont-Ferrand I, 2009)
La diversification des valeurs mobilières a entraîné une dissociation des attributs de l'action. Elle remet en cause certains principes fondamentaux du droit des sociétés, au cœur desquels la question du droit de vote. La suppression du droit de vote entraine des interrogations. Peut-il être considéré comme inhérent à l'action ? Est-il aujourd'hui une condition nécessaire à la qualification d'associé ? Quelles alternatives trouver alors au droit de vote ? Parce qu'elle touche à l'équilibre capital- pouvoir fondant les sociétés par actions, elle remet en cause la cohérence au sein de la société. Parler des incidences de la diversification des valeurs mobilières sur le droit de vote nous conduit à une analyse renouvelée des bases de la société. Le droit de vote n'est pas une condition de l'existence de l'actionnaire mais plutôt un moyen de défendre ses droits pécuniaires. Si le droit de vote ne peut plus être considéré comme essentiel à l'action, ne doit-on pas lui substituer le droit de participer. Par ailleurs, la diversification des valeurs mobilières révèle le fossé grandissant entre les sociétés fermées et les sociétés ouvertes, le droit de vote y perd son importance. Le constat est celui d'une affirmation des spécificités existant entre ces deux types de sociétés. Mais au-delà de ces mutations, il existe une cohérence profonde. Aussi, la reconnaissance d'un principe de droit commun pour les sociétés par actions avec une prise en compte des spécificités par le droit des marchés financiers apparaît à notre sens la situation la plus appropriée.
Keywords: Actionnaires; Droit de vote; France; Sociétés de capitaux; Valeurs mobilières

Rapports organisation mondiale du commerce / Organisation pour l'harmonisation en Afrique du droit des affaires : contribution à l'étude du processus de mondialisation des rapports économiques et commerciaux. - Haidara, Hamzata (Université Nancy 2, 2009)
Le processus de mondialisation a modifié la configuration des relations internationales avec l'apparition de plusieurs organisations qui sont des moteurs de cette évolution. La mondialisation peut être définie comme un processus multidimensionnel caractérisé par une interdépendance dans tous les domaines et conduisant à une concurrence croissante. Elle est ainsi la manifestation du libéralisme international qui constitue à l'heure actuelle l'idéologie dominante. Elle véhicule un "sans frontièrisme" mettant fin au mythe du territoire en tant que cadre principal des relations internationales. Elle défie ainsi l'État en même temps qu'elle utilise son cadre territorial comme un moyen d'expression. L'OMC et l'OHADA sont les deux acteurs principaux de ce processus à des échelons différents : la première au niveau international, la seconde au niveau régional. Ces deux organisations sont-elles alors contradictoires ou bien complémentaires? En d'autres termes, pouvons-nous observer des interactions entre elles? Le principe de l'auto-affirmation de la supériorité traditionnelle du droit international ou universel leur est-il applicable? La concurrence pouvant intervenir entre elles conduit-elle à une cohabitation pacifique ou conflictuelle? Telles sont les questions auxquelles nous allons tenter de répondre. The process of globalization has led to the emergence of new players' international organizations- giving thus a new configuration to the international relations. Globalization can be defined as a multidimensional process characterized by the interdependence in all the areas and leading to an increasing competition. It is the manifestation of international liberalism which is currently the dominant ideology. This process implies the existence of a world without borders which ends the myth of the territory as the main framework of international relations. State is no longer considered as the major player on its own territory. Rather, new policies that include non state players are needed. The WTO and the OHADA are two main players in this process at different levels: the first at the international level, the second at the regional level. Are these two organizations contradictory or complementary? In other words, do they interact? Is the principle of self-assertion of the superiority of traditional international or universal law applicable to them? Does the competition that may occur between them lead to a peaceful or a conflicting coexistence? These are the main issues that the present study will try to tackle.
Keywords: Afrique; Droit communautaire; Droit des affaires; Mondialisation; Organisation mondiale du commerce; Organisation pour l'harmonisation en Afrique du droit des affaires; Organisations internationales; Organisations régionales; Souveraineté des Etats

A critical analysis of problem areas in respect of assets of insolvent estates of individuals - Evans, Roger Graham (University of Pretoria, 2009)
The Law of Insolvency in South Africa is regulated by the provisions of the Insolvency Act 24 of 1936, with foundations in our common law, which has been influenced by different legal systems from Western Europe. But currently there is also other legislation affecting the insolvent debtor and the property in the insolvent estate. The courts too have had to formulate rules to govern aspects of insolvency law in South Africa. These variables created problem areas in insolvency law and in respect of the of the policies upon which the insolvency system hinges. The predominant policy in South African insolvency is the collection of the maximum assets of the debtor for the advantage of creditors in insolvent estates. This strict creditor orientated approach created further problem areas in respect of assets in the insolvent estates of individual debtors. If advantage to creditors cannot be shown in an application for the sequestration of a debtor’s estate, a court will refuse to grant that order. This strict policy overshadows policy concerns in respect of assets in insolvent estates, and regarding exemption law in respect of those assets. This has resulted in insolvency law reformers in South Africa missing the bigger picture, namely, that South Africa is a creditor driven developing society. It is conceivable that in the transformed South Africa, and in the present world economic chaos, there will be an escalation of sequestrations of the estates of individual debtors. Bearing this in mind, a reformed insolvency law system must become more debtor friendly. A change in the philosophy is needed in favour of an exemption policy for insolvent estates. Exemption policy must be based on the interest of the debtor and his dependants, his dignity, creditor and third party interests, social welfare, and human rights imperatives within the South African constitutional framework. Exemption policy must be linked to the policy of a “fresh start” for the debtor. The different policies in insolvency however create a conflict of interest among the different stakeholders, particularly regarding the assets in insolvent estates, thereby creating problem areas. In this thesis several problem areas are identified and critically analysed. The position of property included in, and excluded from, individuals’ insolvent estates is investigated from a brief historical perspective, and in a brief comparative survey of the insolvency systems of the United Kingdom and the United States of America. Acute problem areas are critically analysed in detail, and the constitutional impact on property in insolvent estates is considered in a separate chapter. The South African Law Reform Commission’s review of South African insolvency law is critically analysed in a chapter of this thesis, concluding that the Commission’s review is inadequate. This thesis concludes that there is a need to reform the insolvency system in South Africa and proposes a way forward in respect of property included in, and property excluded or exempt from insolvent estates. This thesis states the law to the end of October 2008.
Keywords: Advantage to creditors; Creditor; Debtor; Disposition of property

Direção material do processo - Claro, Del; Benghi, Roberto (Universidade de São Paulo, 2009)
O juiz tem um dever de direção material do processo que consiste em respeitar os direitos processuais das partes e fomentar o seu exercício. A direção material do processo exige real possibilidade de argumentação das partes sobre todas as alegações de fato e sobre todos os pontos de vista jurídicas contidos na decisão. Existe uma proibição de decisões surpresa. É possível afirmar a presença desse dever judicial no Brasil a partir de duas perspectivas diferentes. Em primeiro lugar, a partir da conexão entre o dever de direção material do processo, uma teoria forte dos direitos processuais e uma concepção liberal de justiça processual. Em segundo lugar, a partir de uma perspectiva comparativa. O processo civil alemão apresenta-se como modelo de um sistema que atende aos requisitos teóricos acima mencionados, além de contar expressamente em seu Código de Processo Civil com a direção material do processo (§ 139, ZPO) e com um remédio contra a violação de direitos processuais (§ 321a, ZPO). Embora o Código de Processo Civil brasileiro não contenha tal dever de forma expressa, a interpretação dos direitos processuais fundamentais contidos na Constituição, aliada à visão teórica desenvolvida, impõe a conclusão da existência do dever de direção material do processo. A direção material do processo só é alcançável a partir de uma concepção de liberalismo político processual capaz de legitimamente conjugar o necessário ativismo processual do juiz com a necessidade de tratar as partes com dignidade. Die materielle Prozessleitung ist eine richterliche Pflicht. In Erfüllung dieser Pflicht muss der Richter die prozessualen Rechten der Parteien respektieren und fördern. Es ist notwendig, dass die Parteien eine reale Möglichkeit der Auseinandersetzung über Tatsachen und Rechtsgesichtspunkte haben. Aus der materiellen Prozessleitung ergibt sich insofern ein Verbot von Überraschungsentscheidungen. In Brasilien können für die Existenz einer richterlichen Befugnis oder Pflicht zur materiellen Prozessleitung zwei verschiedene Gesichtspunkte angeführt werden. Zuerst durch die Verknüpfung der richterlichen Aufgabe, Hinweispflichten zu geben, mit einer starke Theorie von Verfahrensrechten als Ausfluss eines liberalen Verständnis von Verfahrensgerechtigkeit. Zweitens durch eine vergleichende Perspektive. Das deutsche Zivilprozessrecht stellt sich als Modell eines Systems dar, das diese Erfordernisse erfüllt. Es enthält auch in der ZPO die Aufgabe, den Prozess materiell zu leiten (§ 139, ZPO) und gewährt Rechtsbehelfe gegen die Verletzung der Verfahrensrechte (§ 321a, ZPO). Die brasilianische ZPO kennt keine ausdrückliche Pflicht zur materiellen Prozessleitung. Allerdings kann man diese richterliche Hinweispflicht aus prozessualen Grundrechten, in Verbindung mit dem oben erwähnten theoretischen Rahmen ableiten. Die materielle Prozessleitung kann nur durch einen prozessualen politischen Liberalismus erreicht werden, der die notwendige richterliche Einmischung mit der Würde der Parteien in Einklang setzen kann.
Keywords: Deutsches zivilprozess; Direito processual civil; Embargo; Liberalismus; Materielle prozessleitung; Processo civil; Rechte; Verfahrensgerechtigkeit; Zivilprozessrecht; Ônus da prova

A função social da empresa e a composição de interesses na sociedade limitada - Matias, João Luis Nogueira (Universidade de São Paulo, 2009)
Através do presente trabalho, demonstra-se que a função social da empresa é o fundamento e a justificativa para o reconhecimento e a proteção de interesses alheios aos dos sócios na sociedade limitada. Nos três primeiros capítulos, o objetivo é apontar qual o fundamento teórico da funcionalização do direito de propriedade, quais corolários dela decorrem e qual a sua importância para o exercício da empresa. Defende-se que a função social da propriedade é imperativo decorrente da ordem jurídica do mercado, moldada principalmente pelo princípio da solidariedade social. Por sua vez, a função social da empresa é corolário da função social da propriedade. Sustenta-se que a funcionalização do exercício da empresa repercute no exercício da atividade empresarial, acarretando obrigações positivas e negativas aos sócios majoritários (controladores) e administradores das sociedades empresárias, assim como incide sobre o exercício do direito de propriedade de parcelas do capital, do que decorrem obrigações atinentes aos sócios. A partir do capítulo quarto, objetiva-se sistematizar a composição de interesses na sociedade limitada, em abordagem que inclui tanto os conflitos que envolvem os sócios entre si, como os que os vinculam a terceiros, como a própria sociedade, os credores, os empregados, etc. No primeiro aspecto, versa-se sobre: deliberações sociais; o direito de recesso como forma de resolução de conflitos entre os sócios; a dissolução parcial como instrumento para assegurar a liberdade de não permanecer associado; as restrições ao exercício abusivo da administração; a transparência como instrumento de preservação dos interesses dos minoritários; o direito de participação nos lucros e no acervo social em caso de dissolução e liquidação da sociedade; o direito à manutenção da mesma proporção no capital social e o acordo de quotista como instrumento de composição de interesses. No segundo, sobre o conflito de interesses entre a sociedade e o sócio, em razão do exercício do direito de voto; a exclusão dos sócios nas modalidades de resolução da sociedade em relação ao sócio minoritário, da exclusão do sócio majoritário e do sócio remisso; aspectos da composição do capital social; os efeitos externos da sociedade, em abordagem que apreciará as conseqüências da autonomia patrimonial, a responsabilidade dos sócios e administradores e a desconsideração da personalidade jurídica; aspectos da proteção dos interesses dos empregados e da preservação do meio ambiente. A partir da análise doutrinária e jurisprudencial, demonstra-se como o princípio da função social da empresa é importante para a composição de interesses na sociedade limitada.
Keywords: Atividade comercial; Capital social; Conflict of interests; Conflit d'intérêts; Direito de recesso; Direito empresarial; Firm property; Firm social function; Fonction sociale de l'entreprise; Private limited partnership; Property social function; RSE; Resumo em inglês; Sociedade comercial; Sociedade por cotas de responsabilidade limitada; Société Anonyme

Os limites da intervenção judicial na administração das sociedades por ações - Pantano, Tania (Universidade de São Paulo, 2009)
A legislação aplicável às sociedades por ações utiliza conceitos e normas abertas que devem ser interpretadas com base nos princípios que regem as sociedades por ações, considerando, nessa análise, as características específicas da companhia na qual surgiu a controvérsia e as situações que integram e esclarecem a situação controversa levada a conhecimento do Judiciário. A liberdade dos empresários, na condução de suas atividades, tem fundamento no sistema econômico Brasileiro, conforme princípios da Constituição Federal. No entanto, os interesses sociais protegidos pela Constituição Federal exigem que as empresas, especialmente as sociedades por ações, que agregam características institucionais, estabeleçam limites para a condução das atividades das companhias. Da mesma forma, a criação de um ente autônomo e dotado de patrimônio próprio, cria uma separação entre o poder de controle e administração dos bens, direitos e obrigações que integram esse patrimônio e os acionistas que contribuíram inicialmente para sua constituição, motivo pelo qual a condução dos negócios empresariais deve sempre buscar atingir os interesses da companhia e os agentes necessários para realização dessas atividades têm deveres e responsabilidades com os demais acionistas e terceiros afetados pela existência da companhia. Nesse contexto, a atuação do Judiciário se restringe a verificar a ocorrência de atos ilegais de gestão. O Judiciário, no sistema jurídico brasileiro, não podendo interferir no mérito das deliberações, sob pena de infringir o princípio da livre iniciativa e do exercício do poder de controle, que estruturam o sistema legal que regula as sociedades por ações. A responsabilidade dos administradores e controladores que agem de boa-fé nos atos regulares de gestão deve ser preservada em face dos resultados da companhia e os interesses dos demais sócios.
Keywords: Acionista majoritário; Acionista minoritário; Actionnaire majoritaire; Actionnaire minoritaire; Administration; Assembleia geral; Assemblée générale; Commercial law corporate; Corporations; Intervention judiciaire; Intervention judicial; Management; Sociedade anônima (administração); Sociedade comercial; Sociedade por ações (administração); Société par actions

A efetivação dos direitos fundamentais através do processo coletivo: o âmbito de cognição das políticas públicas pelo Poder Judiciário - Canela Junior, Osvaldo (Universidade de São Paulo, 2009)
O presente trabalho objetivou demonstrar que o processo coletivo é o instrumento adequado para a efetivação dos direitos fundamentais sociais. Com a renovação ética representada pela Declaração Universal dos Direitos Humanos, os Estados passaram a institucionalizar os direitos fundamentais, assegurando-lhes eficácia no plano jurídico. Os direitos fundamentais sociais foram concebidos para o estabelecimento da igualdade substancial e para a afirmação da democracia. A morfologia dos direitos fundamentais sociais destaca a existência de núcleos constitucionais de irradiação. Os direitos fundamentais sociais são plena e imediatamente eficazes. O Estado social define os contornos da teoria da separação de poderes. O controle de constitucionalidade erigiu o Poder Judiciário à condição de poder político. A independência e a imparcialidade dos órgãos jurisdicionais impedem a adoção de elementos externos à jurisdição, tais como as questões políticas e a reserva do possível, para afastar o exame da violação dos direitos fundamentais sociais. O princípio da inafastabilidade obriga o exame judicial da violação dos direitos fundamentais sociais. A concessão de tais direitos em processos individuais causa o paradoxo da desigualdade. A análise das políticas públicas faz-se de forma distinta, consoante a fase processual. O âmbito de cognição das políticas públicas pelo Poder Judiciário está restrito à violação, por conduta comissiva ou omissiva do Estado, de direito fundamental social. Os direitos fundamentais sociais são o objeto do processo coletivo, e não as políticas públicas. O provimento jurisdicional realinha as políticas públicas e tende à satisfação plena e coercitiva dos bens da vida em âmbito geral. Il seguente lavoro ha come obiettivo dimostrare che il processo collettivo è lo strumento adeguato per leffettività dei diritti fondamentali sociali. Con la rinnovazione etica rappresentata attraverso la Dichiarazione Universale de Diritti Umani, gli Stati passarono ad istituire i diritti fondamentali, garantendo efficacia nel piano giuridico. I diritti fondamentali sociali furono concepiti per la creazione delluguaglianza sostanziale e per laffermazione della democrazia. La morfologia dei diritti fondamentali sociali distacca l?esistenza dei nuclei costituzionali di irradiazione. I diritti fondamentali sociali sono piena ed immediatamente efficaci. Lo stato sociale delimita i contorni della teoria della separazione dei poteri. Il controllo della consitutizionalità ha eretto il potere giudiziario alla parità del potere politico. Lindipendenza e limparzialità degli organi di giurisdizione impediscono ladozione di elementi esterni alla giurisdizione, tali come le questioni politiche e la riserva del possibili, per allontanare lesame della violazione dei diritti fondamentali sociali. Il principio del non allontanamento obbliga lesame Giudiziario della violazione dei diritti fondamentali sociali. La concessione di tali diritti in processi individuali causa il paradosso della disuguaglianza. Lanalisi delle politiche pubbliche si fa di forma distinta, daccordo con la fase processuale. Lambito della cognizione delle politiche pubbliche da parte del potere Giudiziario è ristretto alla violazione, per condotta missiva od omissiva da parte dello Stato, di diritto fondamentale sociale. I diritti fondamentali sociali sono loggetto del processo collettivo, e non le politiche pubbliche. Il provimento giurisdizionale allinea le politiche pubbliche e tende alla soddisfazione piena e coercitiva dei beni di vita in ambito generale.
Keywords: Direito processual; Direitos humanos; Diritti fondamentali; Diritti fondamentali sociali; Droits fondamentaux; Efficacia; Poder judiciário; Politiche pubbliche; Politique publique; Políticas públicas; Potere Giudiziario; Pouvoir judiciaire; Processo collettivo; Procédures collectives; Questioni politiche; Riserva del possibili; Separazione dei poteri; Separação de poderes; Tutela jurisdicional

La langue et le droit dans les relations internationales - Fernet, Marie (Université de Bourgogne, 2009)
La langue est saisie par le droit en premier lieu dans le cadre des organisations internationales. Plus spécifiquement, les relations internationales en matière commerciale démontrent qu’un champ d’analyse encore vaste reste à défricher. Le choix de la langue est très largement, en matière de commerce international, dépendant de la volonté des parties. La question de l’autonomie de la volonté est donc centrale dans l’étude du lien entre la langue et le droit. Mais le choix de cette langue est souvent fait sans considération des risques linguistiques, et notamment des conséquences en ce qui concerne la mise en œuvre et l’interprétation du contrat. Par ailleurs, les règles concernant l’instance, qu’elle soit étatique ou arbitrale, sont dispersées. La question de la langue n’est de manière générale abordée que de façon accessoire, accidentelle, alors même qu’elle est nécessaire au respect d’un certain nombre de principes, tels que le droit au procès équitable. C’est pourquoi il est nécessaire de réfléchir à la difficulté à exprimer, avec des langues juridiques marquées par les cultures nationales, un droit uniforme, particulièrement en ce qui concerne le commerce international, où le volontarisme étatique trouve moins matière à s’exprimer. Pour cela, des outils sont à la disposition du juriste. En premier lieu, les techniques de traduction, voire de corédaction, des textes juridiques, doivent être exploitées, afin de servir les objectifs de la formulation de la règle de droit, particulièrement lorsqu’il s’agit d’élaborer un droit uniforme. Cela est d’autant plus nécessaire que le droit du commerce international voit l’émergence de concepts autonomes, qu’il sera dans un premier temps difficile à délimiter et à formuler avec l’appareil juridique et linguistique national, marqué par la culture nationale.
Keywords: Arbitrage; Concepts; Contrats internationaux; Interprétation; Langue; Lex mercatoria; Relations internationales; Traduction

Labour law implications of the transfer of an undertaking - Smit, Nicola (University of Johannesburg, 2009)
This thesis provides a comprehensive analysis of the legal, social, and economic consequences of business transfers on employment contracts, focusing on South African law and its comparison with international standards. It critically evaluates the automatic transfer of employment contracts, the protection of employee rights, and the legal complexities surrounding insolvent undertakings.
Keywords: Labour law; Labour legislation; Transfer (Law)

La fragilisation de la propriété immobilière - Forestier, Isabelle (Université de Toulon, 2009)
L'évolution des textes a engendré une fragilisation de la propriété privée immobilière. Il convient de scinder cette recherche en deux parties. La première partie aborde l'intérêt privé et la seconde partie concerne l'intérêt général. Ainsi, il convient tout d'abord d'évoquer l'histoire de la propriété privée afin de comprendre la place réservée à ce droit après sa reconnaissance. Cette étude s'avère indispensable afin de saisir très précisément les raisons qui ont engendré une fragilisation. La multiplication des textes favorables aux personnes en difficultés a vu apparaître un nouvel intérêt qualifié d'intérêt social. Ce nouvel intérêt a entraîné un devoir de justice sociale du propriétaire. Parallèlement, la multiplication de l'utilisation du terme intérêt général a lui aussi engendré une fragilisation. Ainsi, l'étude du droit de l'urbanisme et du droit de l'environnement apparaît essentielle. Ces différentes notions tendent à réduire les pouvoirs du propriétaire. Cette maîtrise des sols est particulièrement étendue puisque le propriétaire participe à la préservation des paysages. Cette protection environnementale favorise le tourisme. Ce dernier domaine engendre aussi une fragilisation de la propriété privée immobilière. The evolution of the texts of laws engendred an embrittlement of the real estate private property. It is advisable to split this research into two parts . The first part approaches the private interest and the second part concerns the general interest. So, it is advisable to evoke first of all the history of the private property to understand the place reserved for the private property after its recognition. This study turns out indispensable to seize very exactly the reasons which engendred at present an embrittlement. The reproduction of texts favorable to the persons in difficulties saw appearing time, the reproduction of the use of the term general interest engendred her an embrittlement. So, the study of the law of the town planning and of the law of the environment seems essential. The capacities of these notions tend to reduce the powers of the owner. This control of grounds is particularly wide because the owner participates in the conversation of the envionmental landscapes. This environmental protection facilates the tourism. This last domain also engenders an embrittlement of the real estate private property.
Keywords: Droit de l'urbanisme; Environnement (protection); Intérêt (droit); Propriété foncière (vente); Propriété immobilière

Le droit à l'exécution forcée : réflexion à partir des systèmes juridiques camerounais et français - Wandji Kamga, Alain-Douglas (Université de Limoges, 2009)
La réflexion sur la nature juridique et l'effectivité du droit à l'exécution forcée s'inscrit dans un mouvement d'ensemble incontournable en droit interne comme en droit international. L' approche comparative fondée sur les systèmes juridiques camerounais et français, enrichie de divers instruments et systèmes internationaux et régionaux, permet d'affirmer que le droit à l'exécution forcée est un droit subjectif et fondamental. Il est reconnu à toute personne titulaire d'un titre exécutoire. La recherche permanente d'un équilibre délicat mais nécessaire entre les droits et intérêts des différentes parties ainsi que la prise en compte des impératifs de l'ordre public et de l'intérêt général, délimitent le domaine du droit à l'exécution forcée. Pour être plus efficace, ce droit doit être construit autour des principes de négociations et de transparence. A ces deux principes nous proposons d' ajouter un autre, celui de la gestion préventive du risque d'inexécution. Consideration of the judirical nature and effectiveness of the right to compulsory execution falls within a general trend that is inescapable as much in internal law as an international law. A comparative approach based in the Cameroon and French legal systems, enriched by diverse instruments and international and regional systems allows us to assert that the right to compulsory executionis a sujective and fundamental right. It is granted to any person who holds an enforceable right. The continuous seeking out of a delicate but necessary balance between the rights and interests of different parties and consideration of the paramountcy of public policy and the general interest, delineate the scope of application of the right to compulsory execution. To be more effective, this right must be built around the principles of negociation and transparency. To these two principles we suggest addind another, that of preventive management of the risk of non-execution.
Keywords: Cameroun; Exécution (droit); France; Recouvement; Recouvrement de créances

Le droit commun des contrats face à l’émergence des droits communautaires africains - Watcho née Keugong Ngueken, Rolande Saurelle (Université de Dschang, 2009)
L’émergence des espaces d’intégration devant aider au renforcement des structures d’intégration économique et politique créées en Afrique au lendemain des indépendances a eu pour conséquence, l’apparition d’un droit matériel essentiellement économique. L’objectif affiché par les différents législateurs communautaires est de moderniser les règles juridiques applicables dans le domaine économique afin de les rendre conformes aux exigences du commerce international et favoriser la sécurité juridique propice au développement des investissements. Or, parce que les contrats constituent les mécanismes juridiques par excellence de l’organisation de la vie économique, ces nouvelles réglementations ne pouvaient manquer d’influencer directement ou indirectement le droit des contrats. L’influence du droit communautaire sur le droit des contrats s’observe en premier lieu dans les réglementations éparses, adoptées aussi bien dans le cadre de l’OHADA, de la CEMAC que de la CIMA. Ces institutions harmonisent en les modernisant les contrats spéciaux dont la plupart ont été hérités du législateur colonial par les Etats membres. C’est ainsi que les perturbations à la théorie générale des contrats relevées dans ces contrats étaient déjà connues dans les Etats membres bien avant l’avènement du droit communautaire. Cependant, cette réaction face aux insuffisances de la théorie générale des contrats ne pouvait s’éterniser au risque de voir celle-ci se vider de sa substance. C’est pourquoi, en second lieu, par un avant-projet d’Acte uniforme, le législateur OHADA offre de s’aligner sur la voie déjà tracée depuis les années 1990 par de nombreux pays ayant adopté le code civil de 1804, en révisant sa partie réservée au droit des contrats. Sans toutefois remettre en cause les principes fondamentaux de la théorie générale des contrats, l’auteur de ce avant-projet propose d’offrir un droit des contrats moderne, moins antagoniste, intégrant les principes de transparence et d’équilibre. Il est question d’apporter des correctifs nécessaires à la rigueur à laquelle a abouti l’interprétation libérale des règles du code civil à l’aune de la théorie de l’autonomie de la volonté. Prenant en compte la diversité du droit communautaire applicable au Cameroun, ce travail met en exergue les transformations que connaît le droit des contrats actuellement applicable et propose les voies et moyens par lesquels la théorie générale du droit des contrats peut évoluer grâce à l’avènement des nouvelles réglementations.
https://dicames.online/jspui/handle/20.500.12177/2203
Keywords: CEMAC; CIMA; Droit commun; Droit communautaire africain; Droit des contrats; OHADA

Rethinking the world trade order: towards a better legal understanding of the role of regionalism in the multilateral trade regime - Abualethem Nsour, Mohammad Fahed (McGill University, 2009)
Regional Trade Agreements (RTAs) have proliferated at an unprecedented pace since the creation of the World Trade Organization (WTO). Although the WTO legally recognizes countries’ entitlement to form RTAs, neither the WTO nor parties to RTAs have an unequivocal understanding of the relationship between the WTO and RTAs. In other words, the legal controversies, the result of uncertainty regarding the application of the WTO/GATT laws, risk undermining the objectives of the multilateral trade system. This thesis tackles a phenomenon that is widely believed to be heavily economic and political. The thesis highlights the economic and political aspects of regionalism, but largely concentrates on the legal dimension of regionalism. The main argument of the thesis is that the first step to achieving harmony between multilateralism and regionalism is the identification of the legal uncertainties that regionalism produces when countries form RTAs without taking into account the substantive and procedural aspect of the applicable WTO/ GATT laws. The thesis calls for the creation of a legal instrument (i.e. agreement on RTAs) that combines all of the applicable law on RTAs, and simultaneously clarifies the legal language used therein. Likewise, the WTO should have a proactive role, not merely as a coordinator of RTAs, but as a watchdog for the multilateral system that has the power to prosecute violating RTAs. The author is aware that political concerns are top priorities for governments and policy makers when dealing with the regionalism problematic. Hence, legal solutions or proposals are not sufficient to create a better international trade system without the good will of the WTO Members who are, in fact, the players who are striving to craft more regional trade arrangements.
Identifier: https://escholarship.mcgill.ca/concern/theses/3r074w80k
Keywords: GATT; International Trade; Regional Trade Agreements (RTAs); WTO

Harmonisation of procedural law in international commercial arbitration - Chang, Mann-Long (University of Stirling, 2009)
The principle of party autonomy is widely accepted in the practice of international commercial arbitration. However, it still encounters certain limitations in its applications, especially for the fact that the demands of natural justice and the public good cannot be neglected by the parties. The various states in the international system have and operate peculiar systems of mandatory rules and public policies, which tend to impart significantly on the arbitral procedure, thereby creating a situation of discordance of outcomes of arbitration in different countries. For this reason, this writer intends to examine ways by which the various procedural laws can actually be harmonised. This thesis shall therefore focus on the discordances and confusion that often arise in the interacion of the various laws that may be applicable to the arbitral process in International commercial arbitration, as well as ways of achieving a harmonisation of these laws.
Keywords: Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; International commercial arbitration

Kurtarma yardımda sigortacının sorumluluğu - Ci̇vi̇r Engi̇n, Mehtap (Marmara Üniversitesi, 2009)
Denizciliğin kendine özgü ihtiyaç ve sorunlarından ortaya çıkmış bir kurum olan kurtarmayardım, TTK. m. 1222-1234'de düzenlenmiş olup köken itibariyle Alman hukukundanalınmıştır. Alman Hukukunun bu konudaki kaynağı ise Türkiye'nin de taraf bulunduğu 1910tarihli Brüksel Konvansiyonu'dur. 1910 tarihli konvansiyona 1967 yılında eklenen protokoleTürkiye taraf olmamıştır. 1989 Londra Konvansiyonuna taraf olma ise gereklidir. Zira 1989konvansiyonu gelişen ve değişen kurtarma teknikleri ve sorunlarını hukuki açıdan çözmekiçin uluslararası alanda düzenlenmiş en son konvansiyondur.Kurtarma yardım ücretinde sorunlardan biri, ücretin nasıl hesaplanacağıdır. Bu husus, 1910Brüksel Konvansiyonu hükümleri ve bu konvansiyona eklenen özel tazminat ve çevre zararınıönleme kriterlerini düzenleyen 1989 Londra Konvansiyonu hükümleri ile düzenlenmiştir.Kurtarma yardım ücreti hesaplanırken mahkeme bu kriterlerin ışığında hakkaniyete uygun birücret belirleyecektir.Kurtarma yardım ücretinin ödenmesi meselesinde önemli bir konu da bu ücretten denizsigortalarının teminat kapsamı doğrultusunda sigortacının sorumluluğu hususudur. Birkurtarma yardım hizmeti gerçekleştirildiğinde öncelikle uygun bir kurtarma yardım ücretibelirlenir. Bu kurtarma yardım ücreti olayın şartlarına göre müşterek avarya teşkil ettiğitakdirde kurtarma ücreti dispeçte alacaklı masasına kaydedilir ve müşterek avaryapaylaşımında yerini alır. Bu paylaşımda sigortacının tazminat sorumluluğu TTK hükümleri,genel şartlar ve İngiliz Hukuku özel şartları (Klozlar) ile York Anvers kuralları ışığındabelirlenir.Kurtarma yardım teşkil etmediği halde ise paylaşıma girmeden kurtarılan değerinsigortacısının kurtarma ücreti ve zararlarından sorumluluğu TTK hükümleri, genel şartlar veİngiliz Hukuku özel şartları (Klozlar) ile belirlenir. Emerged from own specific needs and problems of maritime Salvage, legislated in TTK.m.1222-1234, which has been originated from the German law. The source of German law inthis subject is the Convention dated 1910 in which Turkey is also a party. Turkey has not beenparty of the protocol in 1967 added to Convention dated 1910. Being a party to LondonConvention 1989 is necessary. Because Convention 1989 is the last convention to solvedeveloping and changing salvage techniques and problems from a legal perspective atinternational level.One of the problems of salvage payments is about how to calculate. This issue has beenregulated by provisions of Brussels 1910 Convention and London 1989 Convention whichregulates special compensation and prevention criteria of environmental damage. Whencalculating salvage payment, the court will determine a fair cost in the light of these criteria.An important subject matter of the payment of Salvage is the liability of insurer oriented withthe scope of maritime insurance assurance. When the salvage operation was done paymentwas determined primarily. When general average was established according to thecircumstances of this case this payment is recorded to creditor table at adjustment and takesplace in general average. This shared responsibility in the insurer's indemnity provisions aredetermined in light of the TTK provisions, general terms and specific terms of English Lawand York Antwerp Rules.In the case of without salvage, insurer liability of rescued value from salvage cost and lossesis determined by TTK, general terms and specific terms of English Law without sharing.
Keywords: Deniz araçları; Gemiler; Insurance; Kurtarma; Liability insurance; Naval vessels; Rescue; Responsibility; Ships; Sigorta; Sorumluluk; Sorumluluk sigortası; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Libyan Attitudes towards Islamic Methods of Finance: An Empirical Analysis of Retail Consumers, Business Firms and Banks - Gait, Alsadek Hesain Abdelsalam (Griffith University, 2009)
Libya is a predominately Muslim country where Islamic finance has not yet been established. However, given the current extensive program of financial reform in Libya and the rapid growth and appeal of Islamic finance in comparable economies, there is growing pressure for a system of Islamic finance to be provided. There is then a pressing need for research into the prospects for Islamic finance from a consumer and provider perceptive to inform this debate and thereby meet the needs of policymakers, financial service providers and prospective users. Accordingly, this study of Libyan attitudes towards Islamic methods of finance, the first study attempted in the Libyan context and one of few studies globally, applies a model derived from the Theory of Reasoned Action to analyse attitudes towards Islamic finance. The particular focus is to understand how the Theory of Reasoned Action can be used for predicting and understanding attitudes towards the potential use of Islamic methods of finance by Libyan retail consumers, business firms and banks. Four main research questions are posed to address this objective. First, does awareness of Islamic methods of finance influence attitudes towards the use of Islamic finance? Second, do socioeconomic, demographic and other factors influence attitudes towards Islamic finance? Third, what are the principal motivating factors towards the potential use of Islamic finance? Finally, is religion the major influence on the likelihood of engaging in Islamic finance? Three surveys of 385 retail consumers, 296 business firms and 134 bank managers in Libya are conducted in 2007/08 to achieve this objective. Descriptive analysis and multivariate statistical analysis (including factor analysis, discriminant analysis and binary logistic regressions) are used to analyse the data. The principal findings are that awareness of Islamic methods of finance and socioeconomic, demographic and business characteristics are key determinants of the likelihood of the use of Islamic finance. Further, religion plays a key, though not the only, role in influencing these attitudes. The thesis findings are of key importance in informing future financial industry practice and financial policy formation in Libya.
Accepted: 2018-01-23T02:48:08Z
Keywords: Finance; Financial policy; Financial reform; Islam; Islamic finance; Libya

İslam Deniz Ticaret Hukukunda hukukî sorumluluk - Karaaslan, Muhammet Abdülmecit (Süleyman Demirel Üniversitesi, 2009)
İslam Deniz ticaret hukukunda hukuki sorumluluk? adlı çalısmamızdadeniz ticaret hukuku ile ilgili olarak, İslam hukuku eserlerinde çesitli bölümlerde dağınıkhalde bulunan ?Daman? konusu üzerinde durmaya çalıstık.Konuyu ele alırken giriste özellikle önce, deniz hukuku ile deniz ticaret hukukarasındaki ayrıma dikkat çekerek deniz hukuku ile ilgili konuları dısarıda tuttuk. Daha sonra?İslam deniz ticaret hukuku? kavramını irdeledik. Ardından hukuk-fıkıh arasındaki güncelayrıma göre ?slam hukuku eserlerindeki ibadetlerle ilgili konuları ele almamamız gerektiğinibelirttik. Daha da özele inerek tezimizde; konunun cezai sorumlulukla ilgisini dısarıdatutmak gerektiğinin gerekçelerini sıralamaya çalıstık ve kaynakları nasıl ele alacağımızı izahettikArastırmamızda, birinci bölümde genel olarak ?slam hukuku ve günümüzhukuklarında sorumluluk üzerinde durduk. Sorumluluk fikriyle ilgili ayet ve hadislerden vefıkıh eserlerindeki ilgili tanımları ve sınıflandırmalara dikkat çektik. İslam deniz ticarethukukunun kısa tarihçesini vererek, Rodos deniz Kuralları gibi Roma hukukundan alıntıolduğu iddiasına cevap vermeye çalıstıkİkinci bölümde sözlesmeden doğan hukuki sorumlulukla ilgili olarak, İslamhukukçularının daha ilk yüzyıllardan beri denizde yük/esya ve yolcu tasıma ile ilgili olarak,gemiyi tümden kiralama ve sözlesme yaparak bir bölümünü kiralama veya bizatihi yüktasımayı esas alan kiralama sözlesmelerini farklarıyla birlikte bildiklerini gördük. İslamhukukçuların özellikle sözlesmelerde; geminin adı, varma limanı, yolculuğun süresi, yüksahibinin adı, navlun ücreti ve onun ne zaman ne sekilde ödeneceği vb. hukuki ayrımlarınyük tasıma sözlesmelerinde sözlü veya yazılı olarak olarak ayrıntılı bir sekilde yer almasınısart kostuklarını belirttik.Bilhassa Maliki hukukçuların bu alanda çalısmalarının diğerlerine göre daha fazlaolduğunu gördük. Malikiliğin yaygın olduğu Endülüs İspanyasında ortaya çıkan Consolatedel Mare'da Maliki emir ve hukukçuların büyük etkisi olduğunu karsılastırmalı olarakgöstermeye çalıstık.Üçüncü bölümde haksız fiilden doğan sorumlulukta İslam hukuku eserlerinde?ta'addî ve ifrât? kavramının olduğunu, deniz kazaları, avarya gibi yükün ve gemininkorunması ile ilgili meydana gelen masrafların iki taraf arasında kusurlu olup olmamadurumuna göre bölüsülmesi gerektiğine dikkat çektik. Fırtına, rüzgâr gibi beklenmeyendurumların sebebiyet verdiği kazalarda kusur bulunmasa da sorumlu olunduğunu vemasrafların iki taraf arasında paylasıldığını gördük. Müstakil bir bölüm teskil edecek ölçüdepek yeterli örnekler olmamakla birlikte, son bölümde sebepsiz zenginlesmeden kaynaklananhukuki sorumlulukla ilgili bazı tespitlere yer verdik. We tried to study “Liability Law in the Islamic Maritime Law” in the our exploration. There is a concept called “Daman” that means liability in the islamic maritime law. “Daman” is the same as the compensation of the damage because of the damages given. There are several sections called “Kitabu’d-Daman” in the some Islamic law books. We come across plenty of examples concerned liability that is not only an independent section in the most of Islamic law books but also caused on the contract and unjust action mostly. Some of these examples is concerned about liability in the islamic maritime law. As today in the past as well in the islamic laws the incidents of the maritime law were explained with a comparison with the ones on the land. They paid attention to many principles as well. Fob instance when ships crash each other, they added “unexcpected state”. They also asked like the position of the riders and horse carts bumped into each other on the land at these times horses were under trouble had failure accidents. In addition to this, the sea and ship sourced with the actions they mentioned this in their contract effect. Again, islamic law lecturers, finally with several improvments that were clear in the nineenth and twentieth centuries supplied the ship wholly leased with a contract one section or based on the goods earried as leasing contracts showed law distinctions significantly. Moreover, storing, not suitable to the sea average, shipwreck, goods found under the sea, they paid attention to both sides responsibility when there was an accident. Especially during the reigns of Endulus Spain there was a widespread religious flow called “Malikite” and the Maliki law lecturers stood more than as usual. Muslim judges and others in Katolanya region on the coast of Pacific Ocean of Spain issued rules called “Consolate de’l Mare” today’s maritime laws Like Mediterranean Geography several mixed a widespread culture in such a converted sitiuation maritime law affected under Rhodes rules was rumoured that e neutral investigation put into practice Islamic law people freely their own laws. When Muslims ruled the Mediteranean Area the law of Rome lost control over the region. To some extent there was an influential sitiuation; in other words that was naturally a result.
Keywords: Avarage; Avarya; Beklenmeyen Durum; Consolate Del Mare; Consolate De’l Mare; Contracts; Daman; Daman; Sözlesme; DenizKazaları; Haksız Fiil; Islamic Maritime Law; Kusur-Zarar; Leasing Of Ship; Liability Law; Malikite Law; Sea Accident; Sorumluluk Hukuku; Unexcpected State; Unjust Action; İslam Deniz Ticaret Hukuku

Income splitting, settlements and avoidance: taxing the family on business profits - Loutzenhiser, Glen (Oxford University, 2009)
In a progressive income tax system with an individual tax unit, high-rate taxpayers have an incentive to split income with lower-rate family members to minimise the family’s total tax burden. This raises equity and neutrality concerns. Adopting a spousal tax unit limits the gains from income splitting, but the individual is the better choice on privacy, autonomy, equality, definitional, marriage neutrality and work incentive grounds. Once the individual is chosen as the income tax unit, the control model provides a strong policy basis for attributing both earned and unearned income to individuals. Income splitting, however, undermines this model as well as the individual tax unit. This thesis focuses on the UK’s approach to income-splitting in family businesses. The relevant UK income tax rules, particularly the settlements provisions, are inadequate for the task. Various possible reforms are examined. Incorporating a transfer pricing or ‘reasonableness’ test into the settlements provisions would strengthen these rules, but would make taxpayer compliance with an uncertain regime even more difficult. Another option is to expand the scope of employment tax by moving the borderline between employees and the self-employed or companies. Deeper structural reforms could be made to enhance the neutrality of taxation on different legal forms of economic activity. This would reduce the incentives to incorporate for tax savings, including from income splitting. Integration of income tax and NICs is one such option; a dual income tax is another. A TAAR or GAAR also could be pursued. Ultimately, some combination of these various reform options could provide a partial solution to this challenging issue.
Keywords: Family taxation; Husband and wife; Income splitting; Settlements; Taxation

A balancing act: a framework for participation of non-state actors in the World Trade Organization - Majlessi, Mohammad (McGill University, 2009)
This thesis focuses on the interaction of two categories of non-state actors, private sector corporate actors and non-governmental organizations, with states in the context of the World Trade Organization (WTO) through a lens of public international law. It builds on the premise that the notion of states as the only subjects of international law is not adequate for a modern system of global governance, as it does not reflect the realities of fast-paced globalization and increased co-operation in a world where the boundaries of the private and public are increasingly blurred. It does not necessarily provide solutions for participation of non-state actors in the WTO, but demonstrates that developments in international relations warrant more space for participation of non-state actors, and that the current system of the WTO fails to provide sufficient space for participation. The thesis argues that, for both historical and pragmatic reasons, developments in the areas of GATT and international trade law occurred outside their natural course, leading to the myth of a “self-contained” trade regime not part of public international law. The WTO, unlike its predecessor, enjoys a proper institutional framework and mandate; one can no longer use the excuse of institutional handicap for excluding it from the system of global governance. Liberalization of international trade has far-reaching consequences which are not limited to the trade arena and the WTO, its member states, and scholars of international trade law have to assume their role in the broader context of an international legal order. Non-state actors’ formal participation can contribute to striking a balance between different forces and interests at work in the area of trade liberalization and its interplay with other non-trade issues. After setting the framework for the study, the thesis outlines modes of participation of non-state actors in the creation and modification of WTO law as well as in its enfor
https://escholarship.mcgill.ca/concern/theses/nv9354568
Keywords: Balancing act; International Trade; WTO; World Trade Organization

Médicaments génériques et droit de la concurrence - Petrova, Evgéniya (Université Jean Moulin Lyon 3, 2009)
Face à l’urgence de diminuer les dépenses de santé, le développement des médicaments génériques, moins chers que les médicaments de marque, a été fortement encouragé tant par les institutions communautaires que par les pouvoirs publics nationaux. Le droit de la concurrence accompagne et protège le bon développement des marchés de ces produits. Les règles de concurrence protégent aussi bien la liberté de la concurrence que les intérêts individuels des opérateurs sur ces marchés. La sauvegarde de la liberté de la concurrence est assurée notamment par la sanction de certaines stratégies, adoptées par les laboratoires innovants, qui découragent ou retardent indûment l’entrée des génériques sur le marché. Les intérêts individuels des opérateurs sont préservés notamment par la possibilité d’agir en concurrence déloyale. L’application des règles de concurrence n’est cependant pas aisée et suscite bien des interrogations. L’éventuelle application des règles communautaires relatives aux aides d’Etat à certaines mesures favorisant les génériques au détriment des princeps ou encore la problématique de l’équilibre entre les règles de concurrence et celles de propriété industrielle sont autant de questions qui seront tranchées par les autorités et les juridictions dans les mois et années à venir. Dans les relations entre les médicaments génériques et le droit de la concurrence, les premiers ont aussi un rôle à jouer car ils contribuent non seulement à l’élargissement du champ d’application de ce droit mais également à son évolution à travers notamment l’identification de nouvelles pratiques abusives.
Keywords: Competencia; Competition law; Concurrence; Droit de substitution (pharmacie); Industrie pharmaceutique; Médicaments génériques

Anonim şirketlerin ehliyeti (özellikle ultra vires doktrini ile sınırlandırılması) - Serder, Selen (Ankara Üniversitesi, 2009)
Türk Ticaret Kanunu'nda, ultra vires doktrininin etkisiyle, ticaret şirketlerinin ehliyetlerinin işletme konusuyla sınırlandırılması ölçütüne yer verilmiştir. Buna göre TTK.'nun 137. maddesinde ticaret şirketlerinin ehliyetinin işletme konusu çevresiyle sınırlı olduğu kabul edilmiştir. Anonim şirketlerin ehliyeti de TTK. m. 137 kapsamında işletme konusu çevresiyle sınırlandırılmıştır.İşletme konusu, ana sözleşmede yer alan ve şirketin faaliyet göstereceği iş alanlarını somut olarak ortaya koyan bir kavramdır. Sınırlı ehliyet ilkesinin sakıncalarını gidermek amacıyla işletme konusu kavramını geniş yorumlamak ve işletme konusu kapsamındaki faaliyetleri kolaylaştırmak adına yapılan işlem ve faaliyetleri işletme konusundan saymak gerekmektedir.Anonim şirketlerin ehliyetlerinin kapsam ve sınırları, anonim şirket temsilcilerinin yetkilerinin kapsam ve sınırlarını belirlemesi bakımından da önem taşımaktadır. Anonim şirketin ehliyetinin ve buna bağlı olarak temsilcilerinin yetkilerinin kapsam ve sınırlarının belirlenmesi, anonim şirket ortaklarının, alacaklılarının ve kamu menfaatinin korunması amacına da hizmet etmektedir.Ticaret şirketlerinin ve buna bağlı olarak anonim şirketlerin ehliyet dışı işlemleri, öğretide yer alan baskın görüşe göre yok hükmündedir. Ehliyet dışı yapılan işlemin yok hükmünde kabul edilmesi, bu işlemin hiç doğmadığı ve sonradan onay vermekle bu işleme geçerlilik kazandırılamayacağı anlamındadır.Ticaret şirketlerinin ve dolayısıyla anonim şirketlerin ehliyetinin işletme konusu çevresi ile sınırlandırılması ultra vires doktrini olarak ifade edilmektedir. Ultra vires doktrini İngiliz hukuku kaynaklı olup, şirketler hukuku bakımından şirketlerin hukuki ehliyetinin ana sözleşmelerinde yazılı olan konularıyla sınırlandırılması temeline dayanmaktadır. Günümüzde ultra vires doktrini terk edilmiştir. Nitekim Türk Ticaret Kanunu Tasarısı'nın ticaret şirketlerinin ehliyetini düzenleyen 125. maddesinde ultra vires doktrininin yansıması olan işletme konusu çevresiyle sınırlı ehliyet ilkesine yer verilmemiş olup ultra vires doktrininin yarattığı sakıncaları önlemek adına olumlu bir adım atılmıştır. The rule of limited capacity of companies in the frame of the objects clause, was given a place in the Turkish Commercial Code with effect of ultra vires doctrine. According to this, Article 137 of the Turkish Commercial Code stipulates that capacity of companies are limited in frame of the objects clause of the companies. Capacity of incorporated companies are also limited in frame of the objects clause according to Article 137 of the Turkish Commercial Code.Objects clause is a concept which takes place in the memorandum and which shows scope of the company. In order to remove inconveniences of principle of limited capacity, the transactions and activities made for widely interpreting the concept of objects clause and facilitating the activities in the cover of objects clause, are assumed in the frame of objects clause.Contents and limits of capacity of incorporated companies are significant with regard to defining contents and limits of power of directors of incorporated companies. Defining contents and limits of capacity of incorporated companies and whereupon defining content and limits of power of directors also serve the purpose of protecting share holders and creditors of incorporated companies and public interest Companies? transactions and whereupon incorporated companies? transactions, which are out of capacity are nul and void according to the dominant idea in the doctrine. Assuming the transactions that exceed the capacity of company as nul and void means that this transactions were never made and that further approving such transaction would not make it valid. Limited capacity of companies and whereupon of incorporated companies in frame of objects clause is called ultra vires doctrine. Ultra vires doctrine is of English Law origin and based on the limitation of capacity of the companies by the objects clause of the memorandum, with regard to the law of companies. Today, ultra vires doctrine is relinquished. As a matter of fact, Article 125 of the Scheme of Turkish Commercial Code regulating capacity of the companies did not give place the limited capacity principle which is a reflection of the ultra vires doctrine and took an important step in order to avoid the drawbacks of ultra vires doctrine.
Keywords: Anonim ortaklıklar; Capacity; Commercial law; Ehliyet; Incorporated companies; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Ultra-vires

Status Ambiguity and Conflict in the Market - Tan, David (Emory University, 2009)
My main theoretical contention is that status hierarchies provide a source of guidance to firms for resolving disputes. A status hierarchy implies a system of deference rules among firms. When disputes arise, deference rules can provide a basis for shared expectations and protocols of conduct about how technical ambiguities should be resolved. In many contexts, technical merit is difficult to assess. However, deference rules can operate as social conventions to which firms default, helping to align potentially incompatible expectations. Within this general framework, my dissertation examines how competitors in the semiconductor industry manage uncertain and frequently overlapping patent rights. In practice, patent rights are highly imperfect legal instruments when it comes to demarcating each firm's contributions to innovation in the industry. Patent disputes arise because of the ambiguity this creates about how much of the collective market returns to innovation each firm is entitled to receive. Despite the prolific patenting and propensity for disputes, the industry has remarkably not ground to a halt from runaway litigation. Litigation events, while significant, are rare. I suggest that this degree of order is, at least partly, attributable to status processes. Status can operate as a stabilizing force in the market, helping to generate orderly competition in the face of disputes. To examine whether this is the case in the semiconductor industry, I theorize that disputes are less easily resolved when the parties involved face greater status ambiguity, i.e. are less clearly differentiated from one another in status. Under status ambiguity, deference rules lose the rule-like, universal quality that makes them persuasive in resolving disputes. This has two consequences. First, firms facing low status ambiguity are less likely to be involved in patent litigation than are firms facing high status ambiguity. Patent litigation events represent failures to resolve patent disputes out of court. Second, firms facing low status ambiguity increase their product line sizes more than do firms facing high status ambiguity. The threat of difficult-to-resolve patent disputes represents a cost that can deter firms from bringing products to market.
Permanent URL: https://etd.library.emory.edu/concern/etds/9g54xj191?locale=en
Keywords: Litigation; Patent; Semiconductor; Status

Menkul kıymetleştirme ve varlığa dayalı menkul kıymetler - Turan, Gökçen (Ankara Üniversitesi, 2009)
Menkul kıymetleştirme düzenli nakit akışı sağlayan alacakların likit hale getirilmesi esasına dayanan bir finansman yöntemidir. Bu yöntemde, finansman ihtiyacı içinde olan şirket, düzenli nakit akışı sağlayan alacaklarını özel amaçlı kuruluşa devreder. Alacakları devralan özel amaçlı kuruluş, bu alacakları karşılık göstererek menkul kıymet ihraç eder. Menkul kıymeti satın alan yatırımcılara, vadesi geldiğinde anapara ve faiz ödemeleri, havuzdaki alacaklardan sağlanan gelirlerle yapılır. Böylece, alacakların ilk sahibi olan kaynak şirket, alacaklarının vadesini beklemeden nakit ihtiyacını gidermiş olurken, ihraç edilen menkul kıymeti satın alan yatırımcılar da, güvenilirliği yüksek ve şirketin risklerinden arındırılmış bir alacaklar topluluğunun güvencesi altında sağlam bir yatırım yapmış olurlar.5582 sayılı Kanunun temelinde de, menkul kıymetleştirme yöntemi kullanılarak, konut finansmanı sisteminin ikincil piyasa ayağını oluşturma düşüncesi vardır. Bu kapsamda, ipotekli konut kredilerinin menkul kıymetleştirilmesi sonucunda ihraç edilecek ipotek teminatlı menkul kıymetler ve ipoteğe dayalı menkul kıymetler düzenlenmiştir. İpotek teminatlı menkul kıymetler bir bilanço içi menkul kıymetleştirme özelliği gösterirken, ipoteğe dayalı menkul kıymetler bilanço dışı menkul kıymetleştirme niteliğine sahiptir. Her iki menkul kıymet türünde de, menkul kıymet sahiplerinin korunmasına azami şekilde özen gösterilmiş ve her durumda menkul kıymet sahiplerinin alacaklarını almalarına öncelik verilmiştir. İflasın teminat varlıklara menfi bir etkisinin olması her iki menkul kıymet türünde kanun hükmüyle engellenmiş, gerek teminat havuzu gerek fon portföyü dokunulmaz bir statüye kavuşturulmuştur.Aynı Kanunda, varlık teminatlı menkul kıymetler ve varlığa dayalı menkul kıymetler yoluyla, ipotekli konut kredileri dışındaki alacak çeşitlerinin de menkul kıymetleştirilmesi kabul edilmiştir.Sonuç olarak, menkul kıymetleştirme günümüzün vazgeçilmez finansman metotlarından biridir. Ancak menkul kıymetleştirmeden beklenen faydaların sağlanabilmesi, ana prensiplerine riayet edilerek uygulanmasına bağlıdır. Securitization is a method based on liquidation of receivables enabling regular cash flow. In this method, the company in need of financing transfers such receivables to special purpose vehicle. The special purpose vehicle which take over the receivables issues securities by assuring them. On due the capital and interest payments to the investors purchasing securities are made by the income acquired from the receivables in pool. Therefore, while the company, the originator of receivables, solve the problem of liquidity without waiting for the receivables?s due, the investors make a safe invesment under the assurance of a community of receivables that is highly secure and free of credit risk.On the basis of the Law 5582, there?s also the idea of forming the secondary part of housing finance system by using securitization method. Within this framework, mortgage covered bonds and mortgage backed securities have been regulated, both of which are issued as a result of securitization of residential mortgage loans. Mortgage covered bonds display a characteristic of on-balance sheet, while mortgage backed securities have off-balance sheet property.In both types of securities, utmost great pains to protect securities owners is taken and that securities owners are satisfied under any circumstances is of high priority. Bankruptcy?s negative effect on cover assets is impeded with a law article, thus both cover pool and fund portfolio acquire an immune statute.In the same Law, other types of receivables except residential mortgage loans might be securitised is acknowledged through asset covered bonds and asset backed securities.Consequently, today, securitization is one of indispensible way of financing. However, that expected benefits from securitization can be obtained is possible provided that it is performed with respect to main principles.
Keywords: Asset backed bonds; Asset-backed securitization; Commercial law; Financing; Financing methods; Finansman; Finansman yöntemleri; Menkul kıymetleştirme; Ticaret hukuku; Turkish Law; Türk Hukuku; Varlığa dayalı menkul kıymetler